Three new species of Platfusa Dworakowska (Hemiptera, Cicadellidae, Typhlocybinae) from China - Jiao, Meng; Yu, Xiao-Fei; Yang, Mao-Fa; Yan, Bin (Zootaxa, 2025)
The new leafhopper species Platfusa stella sp. nov., Platfusa lepus sp. nov. and Platfusa semena sp. nov. are described and illustrated based on specimens from China, and a key to all Platfusa species is provided.